Philosophical and Pedagogical Foundations of Media Literacy in the Modern Information Society - Bayniyazov, Alisher (Indonesian Journal Publisher, 2025)
This article explores the philosophical and pedagogical foundations of media literacy in the modern information society. It analyzes key methods for fostering critical thinking and the role of philosophy in shaping value orientations. The study highlights how media literacy influences public consciousness, enabling individuals to critically assess information and resist manipulation. Special attention is given to educational strategies, including interactive teaching methods, project-based learning, and digital literacy training. The philosophical dimensions of media literacy, such as phenomenology, hermeneutics, and ethical considerations, are examined to provide a deeper understanding of information perception. Challenges such as misinformation, algorithmic filtering, and digital inequality are discussed, emphasizing the need for comprehensive educational initiatives. The findings suggest that integrating media literacy into education fosters responsible information consumption and enhances societal resilience against digital-age challenges. Strengthening philosophical and pedagogical approaches is essential for developing media literacy as a crucial skill in contemporary society.